Chloride accelerated Fenton chemistry for the ultrasensitive and selective colorimetric detection of copper. Issue 10 (21st December 2015) - Shan, Zhi; Lu, Mingsheng; Wang, Li; MacDonald, Bruce; MacInnis, Judy; Mkandawire, Martin; Zhang, Xu; Oakes, Ken D.
Abstract : Chloride accelerates copper based Fenton Chemistry resulting in dramatically increased amount of Reactive Oxygen and Chloride Species. Abstract : A highly selective, ultrasensitive (visual and instrumental detection limits of 40 nM and 0.1 nM, respectively), environmentally-friendly, simple and rapid colorimetric sensor was developed for the detection of copper(ii ) in water. This sensor is based on a novel signal-amplification mechanism involving reactive halide species (RHSs) including chlorides or bromides, which accelerate copper Fenton reactions oxidizing the chromogenic substrate to develop colour. The results of this study expand our understanding of copper-based Fenton chemistry.